Kepatuhan perawat dalam cuci tangan dan angka kuman di satu rumah sakit swasta Yogyakarta - Ichtiarini Nurullita Santri; Fatwa Sari Tetra Dewi; Hera Nirwati (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Differences in the number of germs in the palms of nurses according to the level of knowledge and compliance of handwashing in private hospitalsPurposeThis study aimed to measure the difference of germs on the hands of nurses according to level of knowledge and compliance of handwashing in PKU Muhammadiyah Hospital of Yogyakarta.MethodsThis study used observational analytic method with a cross sectional study design. The population in this research was nurses who work in PKU Muhammadiyah Hospital of Yogyakarta totalling 68 people. Measurements used questionnaires and direct observation of handwashing, as well as direct sampling for examination of the number of germs in the palms of nurses.ResultsThere was no difference in the number of germs in the palms of the nurses with knowledge level (p = 0.541), and individual characteristics (p > 0.05). There was a difference in the number of germs in the nurse's hands (p = 0.000) with adherence. The result of observation showed that the lack of compliance of hand washing was due to the lack of awareness of nurses about handwashing.ConclusionThere are differences of germs in the hands of nurses with compliance with handwashing. Therefore, it is necessary to check and supervise handwashing routinely in order to increase awareness of the importance of handwashing by health personnel especially nurses.